DESIGNING ENGLISH SYLLABUS FOR DINIYAH PROGRAM BASED ON STUDENTS’ NEED ANALYSIS AT BABUSSALAM SELAYAR - Naftari, St; Azisah, St; Nurpahmi, Sitti (English Language Teaching for EFL Learners Journal, 2021)
This research aims to design an English syllabus for Diniyah Program at Al-Qur’an Babussalam Islamic Boarding School Selayar. The research design used in this research was Research and Development (R&D) by Richey and Klein. Types of data obtained in this research were qualitative and quantitative. The researchers used a questionnaire and interview guidance as the instrument to obtain the data. This research showed that 1) speaking skill is the priority for the students: In linguistic needs, students’ learning abilities are fair in vocabulary and pronunciation but less in grammar. While vocabulary is the priority, then pronunciation, and the last is grammar. There are twelve real-life topics for learning vocabulary, and pronunciation and basic grammar become integral parts of each lesson. In learning needs, vocabulary learning preferences are memorizing, communicating, listening, and repeating. While learning by imitating, from the dictionary and the recording are the pronunciation learning preferences. In terms of learning style, talking to friends in English, talking in pairs, and role play are the three highest. 2) The design syllabus is based on students’ needs. 3) The syllabus validation by the experts’ judgment clarified that the syllabus had been designed can be used with a bit of revision.